Transforming through leadership: a qualitative study of successful American Indian Alaska Native behavioral health leaders - Brenda J. Freeman; Gary Bess; Candace M. Fleming; Douglas K. Novins (BMC Public Health, 2019)
Abstract Background Effective leadership is vital in the struggle to decrease the behavioral health disparities between the US population and American Indian Alaska Native (AIAN) communities. AIAN communities have a pre-colonization history of highly effective leadership, yet some AIAN leadership traditions have been eradicated through decades of trauma and genocidal efforts. There is a paucity of research on AIAN public health leadership, and most existing research relies on samples of individuals holding leadership positions rather than individuals purposely selected because of their effectiveness. The aim of the study was to investigate the experiences of successful AIAN behavioral health leaders and present an emerging AIAN public health leadership model. Methods Thirty-eight public health leaders in the Substance Abuse and Mental Health Service Administration (SAMHSA) funded Circles of Care project were observed over the course of their three-year leadership role. Stringent criteria for successful community participatory leadership resulted in the selection of 11 of the 38 leaders for inclusion in the study. Ultimately eight leaders (21% of the population of observed leaders) participated in the study. Semi-structured, one-on-one qualitative interviews were conducted. The methods were informed by phenomenology and the data were analyzed using a thematic content analysis approach. Results The analysis resulted in ten themes: Hopeful Vision for the People, Cultural Humility, Awareness of Historical Context, Purpose Driven Work Behavior, Cultural and Bi-Cultural Knowledge, Trusting a Broader Process, Caring Orientation, Holistic Supervision, Community Centered, and Influence Through Education. Respondents were strongly motivated by a desire to help future generations. They described their success in terms of the application of traditional AIAN values such as cultural humility and community orientation, but also relied heavily on task orientation. An emerging AIAN leadership model is presented. Conclusions It is important to encourage AIAN public health leaders to employ leadership research and models conducted or developed in the context of AIAN communities. The emerging model presented in this study could serve as an initial basis for AIAN leadership training. Given the challenging context of AIAN leadership, the lessons taught by these successful leaders could be adapted for use by leaders in non AIAN settings.